The Effect of Different Amounts of Cinnamon Consumption on Blood Glucose in Healthy Adult Individuals - Nildem Kizilaslan; Nihal Zekiye Erdem (International Journal of Food Science)
Background. This study was aimed at investigating the effect of consumption of different amounts of cinnamon on preprandial blood glucose (PrBG), postprandial blood glucose (PoBG), glycosylated hemoglobin (HbA1c), and body mass index (BMI). Methods. This study was carried out on 41 healthy adult individuals. The individuals were divided into 3 groups and monitored for 40 days. The first, second, and third groups were given 1 g/day, 3 g/day, and 6 g/day cinnamon, respectively. Before the beginning of the consumption of cinnamon, HbA1c and PrBG blood tests of the individuals were examined on an empty stomach at family practice centers. Two hours after these tests were carried out and breakfast, PoBG tests were performed. Results. According to the findings of the study, the differences between the average weight measurements, BMI values, and HbA1c values before consumption on days 20 and 40 were not statistically significant in the individuals consuming 1 g, 3 g, and 6 g of cinnamon a day. The difference between the average PrBG measurements was found to be significant in the individuals consuming 6 g of cinnamon per day. The difference between the average PoBG measurements before consumption on days 20 and 40 was significant in the individuals consuming 1 g, 3 g, and 6 g of cinnamon per day. Conclusions. In particular a 3–6 g of cinnamon consumption was found to affect certain blood parameters of individuals positively. Therefore, it is considered to be beneficial to raise awareness of individuals to be conscious to regularly consume cinnamon.